DISKURSUS LETAK APHORISME AL-Quran ( Menelusuri Estetika Ayat-Ayat Metaforis Dalam Kesusteraan Al-Quran) - Wahyu Hanafi Putra (Dialogia, 2016)
Abstract: Holy Qur'an has special language. They are "nature" and "figure of speech". In this case, figure of speech meant metaphor. Metaphor is used to convey a message explicitly. That figure of speech can be found in surah al-Baqarah, al-Kahf, al-Naba 'and al-Balad. Furthermore, the meanings were very diverse and those were analyzed by Balaghah approach. As the result, Holy Qur’an would be a relevant miracle years to years.